(untitled) (Theatrum historiae, 2025)
The topic of this text is the quotidian life of an aristocratic family during the Second World War, that is, between 1939 and 1945. The head of the family was Eduard Mensdorff-Pouilly, the fourth son of Alfons Vladimir Mensdorff-Pouilly and the husband of Giselda, née Collalto e San Salvatore. His family of six children was heavily dependent on his father-in-law, Prince Manfred Collalto, whose financial and material support was necessary to maintain the family’s aristocratic living standards. The text details the family’s way of life during the war, including the upbringing of the children, their social circle, Eduard’s work, the family’s leisure activities, and finally the family’s escape from Czechoslovakia in 1945. Its description of quotidian life is based on Alfred Schütz’s concept of Umwelt and Mitwelt, two parts of an individual Lebenswelt, with particular attention being paid to the Umwelt.